2012
DOI: 10.1097/meg.0b013e328350fae8
|View full text |Cite
|
Sign up to set email alerts
|

Unusually aggressive type 1 gastric carcinoid

Abstract: Gastric carcinoids are rare tumors of the stomach. Gastric carcinoid type 1 is associated with chronic atrophic gastritis, and because of a low metastatic potential, is the most benign type. Death from metastatic disease has been reported in only three patients in a review including 724 cases. The present report refers to a 60-year-old man who was affected by type 2 diabetes mellitus and pernicious anemia and died from metastatic gastric carcinoid type 1. In 1998, a well-differentiated 1.2 cm gastric neuroendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…A second type I G3 NET (case 2), sent to us for histopathologic consultation and later published in detail by Spampatti et al [34], was found during follow-up in a 70-year-old male with an initial diagnosis of multifocal G1 type I NET disease, whose larger (1.2 cm), lympho-invasive nodule, with deep invasion of the submucosa, was successfully resected surgically (wedge resection). Several subsequent endoscopies showed recurrence of intramucosal NETs (carcinoidosis) of 0.2–0.6 cm in size and a Ki67 index of 2% (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second type I G3 NET (case 2), sent to us for histopathologic consultation and later published in detail by Spampatti et al [34], was found during follow-up in a 70-year-old male with an initial diagnosis of multifocal G1 type I NET disease, whose larger (1.2 cm), lympho-invasive nodule, with deep invasion of the submucosa, was successfully resected surgically (wedge resection). Several subsequent endoscopies showed recurrence of intramucosal NETs (carcinoidosis) of 0.2–0.6 cm in size and a Ki67 index of 2% (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…), occasionally intervening over an otherwise indolent type I NET disease, might account for its very rare progression to more ominous, metastatic disease, as it occurred in the 2 G3 NETs (out of 123 cases in the present series, 1.6%). Interestingly, only 0.4% of 724 type I NET cases from the literature considered by Spampatti et al [34] were found to cause tumor-related death. The occurrence of G3 NETs in the stomach is now documented by our findings ([14] and the present study) and those of Lee et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is the opinion that dysplastic cells are less dependent on gastrin stimulation and do not regress in response to reduced circulating gastrin levels. Indeed, a few metastatic cases with a bad prognosis have been reported in type I or II gastric NETs [11, 12]. …”
Section: Discussionmentioning
confidence: 99%
“…However, recent prospective data have shown that gastric NEN constitute the most common gastrointestinal NEN, whereas a subset may develop more aggressive disease [10]. Although some clinical (tumor size) and histopathological (invasion and proliferation index) data can be used to identify patients at risk for an aggressive course, the background of such tumor development is ECLH [17].…”
Section: Discussionmentioning
confidence: 99%
“…Although the great majority of gastric type 1 and 2 NENs follow an indolent course, a subset may become aggressive and develop distant metastases. This has recently been emphasized in a study which showed that gastric type 1 NEN metastatic potential appears to be related to a tumor size of ≥1cm, an elevated Ki-67 labelling index and high serum gastrin levels [10]. …”
Section: Introductionmentioning
confidence: 99%